2015
DOI: 10.1107/s1399004715013073
|View full text |Cite
|
Sign up to set email alerts
|

Iron binding to human heavy-chain ferritin

Abstract: Maxi-ferritins are ubiquitous iron-storage proteins with a common cage architecture made up of 24 identical subunits of five α-helices that drive iron biomineralization through catalytic iron(II) oxidation occurring at oxidoreductase sites (OS). Structures of iron-bound human H ferritin were solved at high resolution by freezing ferritin crystals at different time intervals after exposure to a ferrous salt. Multiple binding sites were identified that define the iron path from the entry ion channels to the oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
105
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(116 citation statements)
references
References 46 publications
10
105
1
Order By: Relevance
“…1B). Consistently, the biomineralization reaction in H-ferritin cages does not require a nucleation site (24,25), and His57 and Glu61 are involved in controlling the access of ferrous ions to the ferroxidase site (6); the reaction at the ferroxidase site is much faster than in L-subunits, with time scales for the iron oxidation in homopolymeric H-cages of <1 s. Even with a low number of H-subunits (1 to 2 per cage), the reaction rate is dominated by the catalytic oxidation of iron occurring at the ferroxidase sites. The formation of ferric clusters of high nuclearity in ferroxidase-active (H or H′) subunits has been inferred from Mössbauer data (26)(27)(28) and NMR data (29,30), but these clusters have never been detected by time-lapse anomalous crystallography approaches.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…1B). Consistently, the biomineralization reaction in H-ferritin cages does not require a nucleation site (24,25), and His57 and Glu61 are involved in controlling the access of ferrous ions to the ferroxidase site (6); the reaction at the ferroxidase site is much faster than in L-subunits, with time scales for the iron oxidation in homopolymeric H-cages of <1 s. Even with a low number of H-subunits (1 to 2 per cage), the reaction rate is dominated by the catalytic oxidation of iron occurring at the ferroxidase sites. The formation of ferric clusters of high nuclearity in ferroxidase-active (H or H′) subunits has been inferred from Mössbauer data (26)(27)(28) and NMR data (29,30), but these clusters have never been detected by time-lapse anomalous crystallography approaches.…”
Section: Discussionmentioning
confidence: 67%
“…In H-type subunits, like human H-ferritin (HuHf), this ideal arrangement of carboxylate side chains is disrupted by replacement of Glu60 with a His, with the concomitant increase in the conformational freedom of the Glu61 side chain (6). Also, Glu57 is replaced by His in HuHf (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This experimental evidence has suggested that the presence of carboxylates at the inner edge of wild-type C3 channels, as well as engineered at the inner edge of C4 channels, determines a favorable electric field for driving Fe 2ϩ into the cage. Accordingly, high-resolution X-ray crystal structures (12,13) have shown two ferrous hexa-aqua ions within vertebrate C3 channels, but only one iron ion within the C4 channels coordinated by four His-169 N⑀2, a water molecule, and a chloride anion (see Fig. 1C).…”
mentioning
confidence: 99%